A case study on beliefs of Organic food consumers - Kaur, Harmandeep (Gyan Management Journal, 2022)
Nowadays, consumers are attempting to make conscious food decisions and favour organic food  over its alternatives. An increasing number of research studies show the interest of the academic  sector in exploring this changed attitude. Due to their importance in attitude formation, the need  arises to comprehend the beliefs of the organic food consumers in depth. The current study tries  to explore consumers’ beliefs (behavioural beliefs, normative beliefs, and control beliefs) about  organic food in detail. As the exploration of these beliefs requires specific observations, this  study is based on qualitative data focusing on consumers’ beliefs about organic food. Data is  collected through personal interviews with the respondents in five cities of Punjab and Haryana  with a total of 20 participants. Results indicate that consumers perceive organic food as healthy,  chemical-free and tasty. High price emerged as a major control belief which limits their purchase  and family is most influential in their purchase decisions. The results imply that a quantitative  study on beliefs about organic food would be useful to investigate these findings in a larger  sample since these findings have several marketing and advertising implications.
Keywords: Organic food; Beliefs; Case study